Designing and Validating a Basketball Learning and Performance Assessment Instrument (BALPAI) - Ibáñez, Sergio J.; Martinez-Fernández, Sergio; Gonzalez-Espinosa, Sergio; García-Rubio, Javier; Feu, Sebastián (Frontiers in Psychology, 2019)
Introduction The assessment of learning in basketball in the PE class, and in training sessions of young players, requires valid, reliable, and trustworthy tools. The purpose of this research was to design and validate the Basketball Learning and Performance Assessment Instrument (BALPAI) that assesses simultaneously decision making, technical execution and efficacy. The play actions are codified using a categorical system, awarding a score for each category (1 = inadequate action; 2 = neutral action 3 = adequate action). An example of a summative procedure for assessing decision making in dribbling is: (1) Dribbling to a place where there is defensive pressure and there is a free teammate able to receive the pass; (2) Dribbling to a place where there is defensive pressure or a free teammate able to receive the pass; (3) Dribbling through a space where there is no defensive pressure and no free teammate able to receive the pass. Methods A pilot study was performed following this procedure. A group of 13 experts participated in the assessment of the 33 elements (66 items) included in the BALPAI. Aiken’s V formula was used to analyze content validity, and internal consistency was calculated using Cronbach’s α. Inter-observer reliability was determined among three observers who used the BALPAI to record the play actions in a 3 × 3 basketball match (N = 45 possessions) and was calculated with the Multirater κfree, obtaining an almost perfect agreement with values between 0.84 and 1. Results The BALPAI has very high internal consistency (0.969), Interobserver reliability was almost perfect (>0.84 in all items) and Aiken’s V coefficient (>0.71 in all items) attained a high value. Conclusion The BALPAI proved to be a valid tool, with high internal consistency and reliability that makes it possible to perform a complete assessment of basketball in PE classes.